Supplemental snack and academic performance of severely wasted pupil beneficiaries - Guillermo, Jay Zion Casanova (Panpacific University : [s.n.], 2018)
This study determined the relationship between the implementation of supplemental snacks and improved nutritional status and academic performance of severely wasted pupil beneficiaries of Rosales District II for the school year 2017-2018. The respondents of the study were the 149 severely wasted pupils of the 15 schools of Rosales District II, Rosales, Pangasinan.
Bibliography: pages 71-74.
CHED-La Union
Keywords: Student welfare